Structure and Function Insight of the α-Glucosidase QsGH13 From Qipengyuania seohaensis sp. SW-135 - Zhai, Xingyu; Wu, Kaijuan; Ji, Rui; Zhao, Yiming; Lu, Jianhong; Yu, Zheng; Xu, Xuewei; Huang, Jing (Frontiers in Microbiology, 2022)
The α-glucosidase play indispensable roles in the metabolic mechanism of organism, prevention and treatment of the disease, and sugar hydrolysis, and are widely used in chemical synthesis, clinical diagnosis and other fields. However, improving their catalytic efficiency and production to meet commercial demand remains a huge challenge. Here we detected a novel GH13 family α-glucosidase, QsGH13, from the deep-sea bacterium Qipengyuania seohaensis sp. SW-135. QsGH13 is highly substrate specific and only hydrolyzes sugars containing alpha-1,4 glucoside bonds. For example, its enzymatic activity for p-nitrophenyl-α-D-glucopyranoside was 25.41 U/mg and the Km value was 0.2952 ± 0.0322 mM. The biochemical results showed that the optimum temperature of QsGH13 was 45°C, the optimum pH was 10.0, and it had excellent biological characteristics such as alkali resistance and salt resistance. The crystal structure of QsGH13 was resolved with a resolution of 2.2 Å, where QsGH13 was composed of a typical TIM barrel catalytic domain A, a loop-rich domain B and a conserved domain C. QsGH13 crystal belonged to monoclinic space group P212121, with unit-cell parameters a＝58.816 Å, b＝129.920 Å, c＝161.307 Å, α＝γ＝β＝90°, which contains two monomers per asymmetric unit. The β→α loop 4 of QsGH13 was located above catalytic pocket. Typical catalytic triad residues Glu202, Asp266 and Glu329 were found in QsGH13. The biochemical properties and structural analysis of QsGH3 have greatly improved our understanding of the catalytic mechanism of GH13 family. This study provides new ideas to broaden the application of α-glucosidase in alcohol fermentation, glycolysis, and other industries.